Regulation of Hypoxia-Inducible mRNAs by the von Hippel-Lindau Tumor Suppressor Protein Requires Binding to Complexes Containing Elongins B/C and Cul2 - Lonergan, Kim M. (American Society for Microbiology, 1998)
The von Hippel-Lindau tumor suppressor protein (pVHL) binds to elongins B and C and posttranscriptionally regulates the accumulation of hypoxia-inducible mRNAs under normoxic (21% O(2)) conditions. Here we report that pVHL binds, via elongin C, to the human homolog of the Caenorhabditis elegans Cul2 protein. Coimmunoprecipitation and chromatographic copurification data suggest that pVHL-Cul2 complexes exist in native cells. pVHL mutants that were unable to bind to complexes containing elongin C and Cul2 were likewise unable to inhibit the accumulation of hypoxia-inducible mRNAs. A model for the regulation of hypoxia-inducible mRNAs by pVHL is presented based on the apparent similarity of elongin C and Cul2 to Skp1 and Cdc53, respectively. These latter proteins form complexes that target specific proteins for ubiquitin-dependent proteolysis.